A Comparative Study of Chest CT With Lung Ultrasound After SARS-CoV-2 Infection in the Assessment of Pulmonary Lesions in Rhesus Monkeys (Macaca Mulatta) - Schilp, Chrispijn M.; Meijer, Lisette; Stocker, Martina; Langermans, Jan A. M.; Bakker, Jaco; Stammes, Marieke A. (Frontiers in Veterinary Science, 2021)
Lung ultrasound (LUS) is a fast and non-invasive modality for the diagnosis of several diseases. In humans LUS is nowadays of additional value for bedside screening of hospitalized SARS-CoV-2 infected patients. However, the diagnostic value of LUS in SARS-CoV-2 infected rhesus monkeys, with mild to moderate disease, is unknown. The aim of this observational study was to explore correlations of the LUS appearance of abnormalities with COVID-19-related lesions detected on computed tomography (CT). Twenty-eight adult female rhesus monkeys infected with SARS-CoV-2 were included in this study. Chest CT and LUS were obtained pre-infection and 2, 7 and 14 days post infection. Twenty-five animals were sub genomic PCR positive in their nose/throat swab for at least one day. CT images were scored based on the degree of involvement for lung lobe. LUS was scored based on the aeration and abnormalities for each part of the lungs, blinded to CT findings. Most common lesions observed on CT were ground glass opacities (GGOs) and crazy paving patterns. With LUS, confluent or multiple B-lines with or without pleural abnormalities were observed which is corresponding with GGOs on CT. The agreement between the two modalities was similar over the examination days. Pleural line abnormalities were clearly observed with LUS, but could be easily missed on CT. Nevertheless, due to the air interface LUS was not able to examine the complete volume of the lung. The sensitivity of LUS was high though the diagnostic efficacy for mild-to-moderate disease, as seen in macaques, was relatively low. This leaves CT the imaging modality of choice for diagnosis, monitoring and longitudinal assessment of a SARS-CoV-2 infection in macaques.